2014
DOI: 10.1182/blood-2013-12-541078
|View full text |Cite
|
Sign up to set email alerts
|

Advanced-stage nodular lymphocyte predominant Hodgkin lymphoma compared with classical Hodgkin lymphoma: a matched pair outcome analysis

Abstract: Key Points• TTP is inferior in patients with advanced-stage NLPHL compared with CHL.• Spleen involvement is associated with an increased risk of secondary aggressive lymphoma in patients treated with ABVD-like chemotherapy.Due to disease rarity, there is limited information regarding the optimal therapy and outcome for patients with advanced-stage nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL). Forty-two patients with NLPHL by the Revised European-American Lymphoma/World Health Organization classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 21 publications
3
62
2
6
Order By: Relevance
“…Chemotherapy alone has not been commonly used in adults with early stage NLPHL, 18 and is the main option for patients with advanced stage. 7,8,19 In this study, patients with stages III-IV who were initially treated received mainly chemotherapy or immuno-chemotherapy (71.1%), a management which is consistent with the international guidelines. 5,6 An unsolved question is the choice of the chemotherapy regimen, in particular between a treatment similar to cHL with ABVD, or a treatment with CHOP, as in indolent NHL.…”
Section: Discussionsupporting
confidence: 61%
“…Chemotherapy alone has not been commonly used in adults with early stage NLPHL, 18 and is the main option for patients with advanced stage. 7,8,19 In this study, patients with stages III-IV who were initially treated received mainly chemotherapy or immuno-chemotherapy (71.1%), a management which is consistent with the international guidelines. 5,6 An unsolved question is the choice of the chemotherapy regimen, in particular between a treatment similar to cHL with ABVD, or a treatment with CHOP, as in indolent NHL.…”
Section: Discussionsupporting
confidence: 61%
“…The BCCA reported a matched control outcome analysis of patients with NLPHL (n 5 42) or cHL (n 5 82) treated with ABVD or ABVD-like chemotherapy. 49 At 15 years, there was a trend toward superior PFS for cHL compared with LPHL (72% vs 44%; P 5 .096). The largest series of patients with advanced disease is from the GHSG, comparing outcomes of 83 patients with NLPHL with outcomes of 3083 patients with cHL included in prospective trials.…”
Section: Org Frommentioning
confidence: 91%
“…Recent data indicate that progression to a process with features of THRLBCL is associated with a more aggressive clinical course, and requires different management, such that the term NLPHL in this setting may not be sufficient. 147,148 However, cases with only focal diffuse areas are not considered transformation. It is also of interest that aside from their immunomorphologic appearance, GEP and array comparative genomic hybridization studies have shown similarities between NLPHL and THRLBCL, suggesting a relationship to each other, in spite of other major differences.…”
Section: Ebv 1 T-cell and Nk-cell Lymphomasmentioning
confidence: 99%